1999
DOI: 10.1016/s0008-6363(99)00256-4
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome proliferator-activated receptor γ C161→T polymorphism and coronary artery disease

Abstract: We report that the PPAR gamma C161-->T substitution is associated with a reduced CAD risk, particularly among CT heterozygous patients, but not with obesity in Australian Caucasian patients. It implicates that the PPAR gamma may have a significant role in atherogenesis, independent of obesity and of lipid abnormalities, possibly via a direct local vascular wall effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
96
4
2

Year Published

2002
2002
2010
2010

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(110 citation statements)
references
References 27 publications
8
96
4
2
Order By: Relevance
“…Therefore PPARg is a potential candidate gene for the link between diabetes mellitus and the premature atherosclerosis in patients with diabetes mellitus. This hypothesis is supported by the findings of Wang et al (19), who reported an association of a C161T polymorphism in the PPARg gene with a reduced risk of coronary artery disease in patients with and without diabetes. Moreover, it was recently shown that treatment with troglitazone reduces the neointimal tissue proliferation after coronary stent implantation in patients with type 2 diabetes suggesting a causal involvement of PPARg in the development of atherosclerotic plaque (31).…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Therefore PPARg is a potential candidate gene for the link between diabetes mellitus and the premature atherosclerosis in patients with diabetes mellitus. This hypothesis is supported by the findings of Wang et al (19), who reported an association of a C161T polymorphism in the PPARg gene with a reduced risk of coronary artery disease in patients with and without diabetes. Moreover, it was recently shown that treatment with troglitazone reduces the neointimal tissue proliferation after coronary stent implantation in patients with type 2 diabetes suggesting a causal involvement of PPARg in the development of atherosclerotic plaque (31).…”
Section: Discussionsupporting
confidence: 73%
“…We could not confirm this finding in our study population. One explanation for these divergent findings could be that our study was exclusively performed with patients with diabetes, whereas Wang et al (19) mainly studied patients without diabetes. Moreover, the frequency of the C161T polymorphism was lower in our study (Group 1: 12.8%, Group 2: 14.1%) as compared with the C161T frequency (27.7%) reported in the previous study (19).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…24 Interestingly, this study did not consider the Ala allele and found that the protective advantage was mainly among the C1431T heterozygotes, with C1431 and TT homozygous individuals each having evidence of increased disease. Based on our findings, we would predict that individuals homozygous for the T allele would have increased disease because of an increased ratio of T to Ala alleles, whereas CT heterozygotes, in contrast, would be expected to have an approximately equal proportion of opposing Ala alleles and would thus be relatively protected.…”
Section: Discussionmentioning
confidence: 76%
“…Yet the SNP has been reported to be associated with lipoprotein profiles (Wang et al 1999). The interaction effect between the 161C/T variant and apoE-4 genotype on serum cholesterol level has been suggested (Peng et al 2003).…”
Section: Resultsmentioning
confidence: 99%